Promoting Digital Inclusion Through the NBN - Corbin, Teresa (Journal of Telecommunications and the Digital Economy, 2019)
This is the speech given by Ms Corbin at the TelSoc NBN Futures forum held in Melbourne on 22 October 2019. She spoke on how to include all Australians in the National Broadband Network through more affordable pricing of services, continued and improving reliability of access, and an evolution of the Universal Service Obligation.